University Climate Curriculum Knowledge Sharing and Co-Design Workshop for RUFORUM Curriculum Platform - Grossi, Amanda; Dinku, Tufa; Hansen, Jim; Nakayiwa, Florence; Mwanjalolo, Majaliwa; Crane, Todd A.; Zougmoré, Robert B.; Solomon, Dawit (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Tackling the climate crisis means equipping the youth with the knowledge and skills they need to manage climate risk. Universities across Africa have an enormous role to play towards this end. By equipping the next generation of researchers, policymakers, and leaders with the knowledge and skills they need to build resilient societies, education systems represent an important avenue for sustained capacity building beyond project life cycles.